Bibliometric analysis of research themes and trends in childhood autism spectrum disorders from 2012 to 2021 - Zhao, Junqiang; Lu, Yi; Wu, Xingyang; Zhou, Fujun; Fei, Fangqin; Wu, Xiaoyan; Ding, Xiufang; Wang, Minli (Frontiers in Public Health, 2022)
Background Autism spectrum disorders (ASD) are heterogeneous neurodevelopmental conditions that affect people worldwide. Early diagnosis and clinical support help achieve good outcomes. However, medical system structure and restricted resource availability create challenges that increase the risk of poor outcomes. Understanding the research progress of childhood ASD in recent years, based on clinical literature reports, can give relevant researchers and rehabilitation therapists more resonable research guides. Objective This bibliometric study aimed to summarize themes and trends in research on childhood ASD and to suggest directions for future enquiry. Methods Citations were downloaded from the Web of Science Core Collection database on childhood ASD published from 1 January 2012, to 31 December 2021. The retrieved information was analyzed using CiteSpace.5.8. R3, and VOS viewer. Results A total of 7,611 papers were published across 103 areas. The United States was the leading source of publications. The clusters that have continued into 2020 include coronavirus disease 2019, gut microbiota, and physical activity, which represent key research topics. Keywords with frequency spikes during 2018–2021 were “disabilities monitoring network,” “United States,” and “caregiver.” Conclusions The Autism and Developmental Disabilities Monitoring Network in the United States can be used as a reference for relevant workers worldwide. An intelligent medical assistant system is being developed. Further studies are required to elucidate challenges associated with caring for a child with ASD.